Nanometric material removal using electrokinetic phenomenon - Leo, Cheng Seng (2012)
Material removal at the sub-micron level has been a topic of interest in the past few years, particularly with respect to the fabrication of miniaturized devices. While numerous techniques have been developed and refined from their larger meso-scale counterparts (e.g. polishing), most have inherent limitations (such as the introduction of scratches from polishing) which may render these processes to be less attractive. In this work, a novel non-contact technique (where the machining tool is not in contact with the workpiece [1-4]) of using electrokinetic phenomenon for precise material removal (a.k.a electrokinetic material removal process) at rates in the order of nanometers/min is introduced. The technique involves movements of abrasive particles in a fluidic flow, under the influence of an AC electric field with a DC offset, to collide with the surface of the material to achieve material removal. Results showed that the technique is feasible in achieving material removal up to a depth of several hundred nanometers. Parametric studies on the material removal, which include material removal rate (MRR) and surface roughness (SR), were carried out and documented. A semi-empirical model on the material removal rate (MRR) was subsequently proposed after the dominating material removal mechanism was identified. The model was further validated with additional experimental results to show its predictive capability. With no chemicals involved in the process, the technique offers the further attraction of being a benign nano-manufacturing process with potential usage in the microelectromechanical systems (MEMS) areas.